Rational thresholding of circulating tumor DNA concentration for improved surveillance of metastatic breast cancer - Martens, G.A.; Demol, J.; Dedeurwaerdere, F.; Breyne, J.; De Smet, K.; De Jaeger, P.; De Smet, D. (ESMO open, 2024)
The use of circulating tumor DNA (ctDNA) concentration for metastatic cancer surveillance is promising, but uncertainty remains about cut-offs with clinical validity. This observational study recruited 136 subjects with advanced metastatic breast cancer (irrespective of ERBB2/hormone receptor status) for sequencing of their primary tumor in search for PIK3CA hotspot variants amenable for monitoring by droplet digital PCR (ddPCR). The study analyzed 341 on-treatment samples from 19 patients with PIK3CA variants H1047R or E545K enrolled for long-term (median 85 weeks, range 13-125 weeks), frequent (every 3-5 weeks, median of 14 time points per subject, range 2-29) blood sampling for ctDNA quantification by ddPCR, orthogonally validated by deep sequencing. The diagnostic accuracy of ctDNA versus cancer antigen 15-3 (CA15-3) concentrations to predict disease progression within 12 weeks was investigated using receiver operating characteristic (ROC) analysis. Likelihood ratios were used for rational selection of ctDNA result intervals. ctDNA [area under the ROC curve (AUC) 0.848, 95% confidence interval (CI) 0.791-0.895] showed superior diagnostic performance than CA15-3 (AUC 0.670, 95% CI 0.601-0.735, P < 0.001) to predict clinical progression within 12 weeks. ctDNA levels below 10 mutant allele copies/ml had high negative predictive value (88%), while levels above 100 copies/ml detected 64% of progressions 10 weeks earlier versus standard of care. Logistic regression analysis indicated complementary value of ctDNA and the presence of two consecutive CA15-3 rises, resulting in a model with 86% (95% CI 74% to 93%) positive predictive value and a clinically meaningful result in 89% of blood draws. Intensive ctDNA quantification improves metastatic breast cancer surveillance and enables individualized risk-based scheduling of clinical care. •CA15-3 is widely used to monitor breast cancer treatment and recurrence despite its limited specificity.•ctDNA levels show diagnostic value for cancer progression but decision thresholds for individual patients were lacking.•We present a novel statistical approach for retrospective analysis of real-world data on ctDNA levels in cancer surveillance.•In metastatic breast cancer, ctDNA levels below (above) 10 copies/mL (100 copies/mL) have high NPV (PPV) for progression.•Frequent long-term monitoring of ctDNA levels holds value for risk-informed scheduling of standard care in metastatic cancers.